Best Answer

how to solve 3y = 6x - 9

You can't solve for both X and Y with only a single equation. You need two equations with both X and Y. With the one shown equation you can get

y = (6x - 9)/3 = 6x/3 - 9/3 = 2x- 3

6x = 3y+9,

then x = (3y + 9)/6 = 3y/6 + 9/6 = y/2 + 3

If there were a second equation with X and Y we would be able to replace X or Y with one of the above expressions and solve for the other variable.

Q: How do you solve 3y equals 6x - 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Ok, sure. So:6x-3y-9=0-3y-9=-6x+0-3y=-6x+9y=2x-3

6x + 3y = -9 So 3y = -6x - 9 or y = -2x - 3 So the slope of the given line is -2 Therefore, the slope a any parallel line is also -2.

2x+6x=-9 => 8x=-9=> x=-8/9

there are several methods .... elimination, substition, graphing, and cramer's rule for substitution : (1st eq) 6x - 3y = 9 (2nd eq) 9y = -3x + 2x simplifies into 9y = -x or x = -9y substitute this into the (1st eq) 6(-9y) - 3y = 9 -54y - 3y = 9 -57y = 9 y = -9/57 =-3/19 now use this to find the x value ... x = -9y = -9(-3/19) x = 27/19 thus the answer is the ordered pair (27/19, -3/19)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

Related questions

Ok, sure. So:6x-3y-9=0-3y-9=-6x+0-3y=-6x+9y=2x-3

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

6x + 3y = -9 So 3y = -6x - 9 or y = -2x - 3 So the slope of the given line is -2 Therefore, the slope a any parallel line is also -2.

2x+6x=-9 => 8x=-9=> x=-8/9

Slope intercept form is y=mx+b To convert 6x-3y-9=0 into this form, we must first isolate y. We do this by adding 3y to both sides. Now we have 3y=6x-9 To simplify this, we divide both sides by 3. The answer is now y=2x-3

(x, y) = (3, 7) is a solution.

9+6x = 25-2x 6x+2x = 25-9 8x = 16 x = 2

16x+9 without the rest of the equation, what this equals, I can't solve

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

there are several methods .... elimination, substition, graphing, and cramer's rule for substitution : (1st eq) 6x - 3y = 9 (2nd eq) 9y = -3x + 2x simplifies into 9y = -x or x = -9y substitute this into the (1st eq) 6(-9y) - 3y = 9 -54y - 3y = 9 -57y = 9 y = -9/57 =-3/19 now use this to find the x value ... x = -9y = -9(-3/19) x = 27/19 thus the answer is the ordered pair (27/19, -3/19)

If you mean: 6x+3y = -9 then the perpendicular slope works out as 1/2 or 0.5